Representation of Colors in the Blind, Color-Blind, and Normally Sighted - Shepard, Roger N.; Cooper, Lynn A. (Psychological Science, 1992)
Human adults with normal vision, with three types of color-blindness, or with complete absence of vision since birth rank-ordered the similarities of all pairs of colors corresponding to nine hue names. When presented with the names only, subjects with any color vision produced rankings for which multidimensional scaling yielded Newton's color circle. When subjects were presented with the colors themselves, the recovered color circle remained the same for the normally sighted but collapsed along the red-green dimension for the color-blind. Based on their rankings by color names, the totally blind subjects all fell outside the range of the color-normal subjects but partly overlapped the color-deficient subjects; a rare rod monochromat roughly approximated the color-normal subjects. These results, along with those of Marmor (1978) and Izmailov and Sokolov (this issue), suggest how visual experience, language, and innate structure contribute to the mental representation of colors.